Racial/Ethnic and Socioeconomic Differences in Bone Loss Among Men. (December 2014) - Araujo, Andre B; Yang, May; Suarez, Elizabeth A; Dagincourt, Nicholas; Abraham, Jonathan R; Chiu, Gretchen; Holick, Michael F; Bouxsein, Mary L; Zmuda, Joseph M
ABSTRACT As men age, they lose bone and are susceptible to fracture. Despite having lower fracture rates than women, men have worse fractures than women do. Racial/ethnic and socioeconomic status (SES) disparities in fracture rates exist, yet data on rates of bone loss by race/ethnicity and SES among men are limited. We examined annualized percentage change in bone mineral density (%ΔBMD) at the hip (N = 681), spine (N = 663), and forearm (N = 636) during 7 years of follow‐up among men aged 30–79 years at baseline. Multivariable models tested whether race/ethnicity, income, or genetic ancestry predicted annualized %ΔBMD after controlling for an extensive set of covariates. Annualized %ΔBMD ranged from −0.65(0.04)% (femoral neck) to +0.26(0.03)% (1/3 distal radius), and changes were consistent across age groups with the exception of the ultradistal radius, where annualized declines increased with age. Neither self‐identified race/ethnicity nor genetic ancestry were associated with annualized %ΔBMD. In contrast, income was strongly associated (dose‐response) with annualized %ΔBMD at total hip (independent of confounders, self‐identified race/ethnicity, and genetic ancestry). Fully adjusted least‐square mean change in annualized %ΔBMD at the total hip were −0.24(0.12)% and −0.16(0.06)% steeper among men with low and moderate incomes, respectively, than among men with higher incomes (overall p = 0.0293). Results show a linear decline in bone that begins relatively early in life among men, that rates of bone loss do not vary with race/ethnicity (self‐identified or "objectively" measured), and that income plays an important role in relation to bone loss at the hip. These data suggest that fracture risk in men may be driven in part by income‐related differences in bone loss, but also, that the known higher fracture risk among white men is not the result of racial/ethnic differences in bone loss, but rather, early life exposures that lead to attainment of higher peak bone mass among minorities. © 2014 American Society for Bone and Mineral Research.